Activity determination, kinetic analyses and isoenzyme identification of gamma glutamyltransferase in human neutrophils - (:unkn) unknown (My University, 2005)
Gamma-glutamyltransferase (GGT, EC 2.3.2.2) which hydrolyzes glutathione (GSH), is required for the maintenance of normal intracellular GSH concentration. GGT is a membrane enzyme present in leukocytes and platelets. Its activity has also been observed in human neutrophils. In this study, GGT was purified from Triton X-100 solubilized neutrophils and its kinetic parameters were determined. For kinetic analyses of transpeptidation reaction, gamma-glutamyl p-nitroanilide was used as the substrate and glycylglycine as the acceptor. Apparent K(m) values were determined as 1.8 mM for gamma-glutamyl p-nitroanilide and 16.9 mM for glycylglycine. The optimum pH of GGT activity was 8.2 and the optimum temperature was 37 degrees C. It had thermal stability with 58 % relative activity at 56 degrees C for 30 min incubation. L-serine, in the presence of borate, was detected as the competitive inhibitor. Bromcresol green inhibited neutrophil GGT activity as a noncompetitive inhibitor. The neutrophils seem to contain only the isoenzyme that is present in platelets. We characterized the kinetic properties and compared the type of the isoenzyme of neutrophil GGT with platelet GGT via polyacrylamide gel electrophoresis (PAGE) under a standard set of conditions.
Keywords: Humans; Glutathione; Kinetics; Electrophoresis, Polyacrylamide Gel; Neutrophils; gamma-Glutamyltransferase; Blood Platelets; Chromatography, Gel; Isoenzymes